SENGKETA JUAL BELI TANAH BERSTATUS SURAT KETERANGAN TANAH: KEDUDUKAN HUKUM DAN PENYELESAIANNYA DALAM REGULASI HUKUM POSITIF DAN HUKUM ADAT DAYAK - Ahmad Setiawan; Agus Mulyawan; Nuraliah Ali (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
Disputes over land occur in almost every region in Indonesia. One of the cases of legal problems in the field of buying and selling land is the dispute over the sale and purchase of land with the status of a land certificate with overlapping ownership. Dispute resolution methods are litigation or through court and non-litigation or outside the court such as through Nganju Dayak customary law. This study aims to examine how the legal position of land ownership certificates (SKT) is in the perspective of positive law in Indonesia and how to resolve it according to the Adat law of the Dayak Ngaju of Central Kalimantan. This type of research is empirical juridical legal research. The types or sources of data used are primary data and secondary data. The research instruments used were interviews and library research. Data obtained based on library research and field data were analyzed by qualitative descriptive analysis. The position of SKT is based on positive law in Indonesia as stated in Article 76 paragraph (3) Permenag No.3/1997, a certificate of rights does not meet the requirements to be considered a statement of physical ownership of a land parcel if it does not fulfill the six specified conditions. Land which is based only on HCS ownership, does not have sufficiently strong evidence of ownership of the land and is directed to increase the legality of ownership certificates or SHM as proof of ownership that is authentic and legal with legal certainty. Settlement of land sale and purchase disputes based on customary law of the Dayak Nganju through Kedamangan Jekan Raya is pursued by prioritizing the peace process and prioritizing the principle of kinship, the decision does not cause resentment and dissatisfaction, without resentment which ends in the breakup of good relations between the two.